2023
DOI: 10.20944/preprints202303.0094.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serological Prevalence of Hepatitis C Virus among Febrile Patients Attending a General Hospital in Emohua LGA, Rivers State, Nigeria

Abstract: This study was to determine the prevalence of hepatitis C virus (HCV) among febrile patients attending a General Hospital in Emohua LGA, Rivers State, Nigeria. Eighty-nine patients, including 31 males and 58 females, aged 2 to 60 years, were recruited for this study. Blood samples were screened for antibodies to hepatitis C virus (HCV) using a commercially available anti-HCV-Ab enzyme-linked immunosorbent assay (ELISA) based kits following the manufacturer's description. The results showed an overall prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 49 publications
4
6
2
Order By: Relevance
“…This observation is discordant with the reports of Umumararungu et al (2017), who documented a higher prevalence among married and divorced/widowed people than singles. Our observation supports previous studies in Nigeria, which observed higher rates among singles than married (Abeni et al, 2020; Okonko et al, 2022; Okonko & Ernest Nwagwu, 2023). This high prevalence may imply that transmission of HEV via sex is essential.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This observation is discordant with the reports of Umumararungu et al (2017), who documented a higher prevalence among married and divorced/widowed people than singles. Our observation supports previous studies in Nigeria, which observed higher rates among singles than married (Abeni et al, 2020; Okonko et al, 2022; Okonko & Ernest Nwagwu, 2023). This high prevalence may imply that transmission of HEV via sex is essential.…”
Section: Discussionsupporting
confidence: 92%
“…The coinfection rate of HIV/HCV in this study was significantly higher among older participants, which differs from a study reported by Ogbodo et al (2015) in Ughelli, Delta State, Nigeria and Abeni et al (2020) in Port Harcourt, Nigeria. However, it corroborates our recent study in Port Harcourt, Nigeria (Okonko et al, 2022) and Ogbakiri, Emohua LGA, Rivers State, Nigeria (Okonko & Ernest Nwagwu, 2023). It also supports Tessema et al’s (2010) study in Plateau State, Nigeria (Odjimogho et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Infection with the Hepatitis B virus (HBV) is a signi cant global health burden (Im et al, 2022;Okonko et al, 2023b). An estimated 296 million people had chronic HBV infection in 2019, and more than 820,000 people died due to HBV (WHO, 2021).…”
Section: Introductionmentioning
confidence: 99%